2021
DOI: 10.1002/rcs.2307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of da Vinci robot‐assisted lymph node surgery than conventional axillary lymph node dissection in breast cancer – A comparative study

Abstract: Background: da Vinci robot-assisted axillary lymph node dissection (dVALND) can be a minimally invasive technique to minimize post-operative complications.Objective: To explore the clinical efficacy of dVALND in breast cancer (BC) patients for mitigating the postoperative complications than conventional ALND.Methods: Total 60 female patients with BC were admitted to our hospitals since September 2018, and these patients segregated into two groups of 30 patients each. Modified radical mastectomy for BC was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Technologic innovations in recent years have led to improved imaging and navigation that has increased the accuracy, reach, and diagnostic yield of endoscopic sampling. The most recent of advances, robotic bronchoscopy, follows a national and global trend of the proliferation of robotic-assisted surgeries for thoracic [ 7 , 8 ] and extra-thoracic pathology [ 9 , 10 ] as well as oncologic staging such as axillary lymph node dissections [ 11 ]. The accompanying literature thus far demonstrates superiority or non-inferiority in numerous metrics including patient outcomes and medical cost compared to open or laparoscopic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Technologic innovations in recent years have led to improved imaging and navigation that has increased the accuracy, reach, and diagnostic yield of endoscopic sampling. The most recent of advances, robotic bronchoscopy, follows a national and global trend of the proliferation of robotic-assisted surgeries for thoracic [ 7 , 8 ] and extra-thoracic pathology [ 9 , 10 ] as well as oncologic staging such as axillary lymph node dissections [ 11 ]. The accompanying literature thus far demonstrates superiority or non-inferiority in numerous metrics including patient outcomes and medical cost compared to open or laparoscopic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the robotic BABA, many studies have reported that robotic thyroidectomy is a good surgical method in terms of surgical stability and favorable surgical completeness [12,[15][16][17]. Furthermore, robotic excellent surgical stability and completeness have also been reported in other part surgery [18]. Our hospital adopted the da-Vinci Xi system in December 2018 and began performing robotic BABA thyroid surgery with a single endocrine surgeon [19].…”
Section: Introductionmentioning
confidence: 94%
“…The role of the minimally invasive technique in improving BC patients' quality of life and in minimizing post-operative complications is also analyzed in a recent comparative study by Chen and colleagues, who have reported a decreased incidence of lymphedema after the Da Vinci Robot-assisted axillary lymph-node dissection during NSM. [100].…”
Section: Conservative Mastectomymentioning
confidence: 99%